Beyond a Joke
VIII, 212 p.
Keywords: Humour is pervasive in contemporary culture, and is generally celebrated as a public good. Yet there are times when it is felt to produce intolerance, misunderstanding or even hatred. This book brings together, for the first time, contributions that consider the ethics as well as the aesthetics of humour. The book focuses on the abuses and limits of humour, some of which excite considerable social tension and controversy. Beyond a Joke is an exciting intervention, full of challenging questions and issues.